Spatial and social mobility - Matthias Wrede; Rainald Borck (European Regional Science Association (ERSA), 2015)
This paper analyzes the relationship between spatial mobility and social mobility. It develops a two-skill-type spatial equilibrium model of two regions with location preferences where each region consists of an urban area which is home to workplaces and residences and an exclusively residential suburban area. The paper demonstrates that both segregation and regional income inequality are negatively correlated with relative regional social mobility. In the model, segregation is driven by differences between urban and residential areas in commuting cost differences between high-skilled and low-skilled workers, whereas regional income inequality also depends on the magnitude of the productivity gap of low-skilled workers. A larger productivity gap does not affect segregation, but causes higher income inequality and lower relative mobility in the respective region.
Keywords: J62; R13; 330; social mobility; spatial mobility; segregation; inequality